Patrilocal Residence and Female Labour Supply - Andreas Landmann; Helke Seitz; Susan Steiner (Institute of Labor Economics (IZA), 2017)
We examine the role of intergenerational co-residence for female labour supply in a patrilocal society. To account for the endogeneity of women's co-residence with parents or in-laws, we exploit a tradition in Central Asia, namely that the youngest son of a family usually lives with his parents. Using data from Kyrgyzstan, we therefore instrument co-residence with being married to a youngest son. We find the effect of co-residence on female labour supply to be negative and insignificant. This is in contrast to the previous literature, which found substantial positive effects in less patrilocal settings. Women who co-reside in Kyrgyzstan have more children, spend similar time on housekeeping tasks and child care, and invest more time in elder care compared with women who do not co-reside. These mechanisms appear to be inherently different from those in less patrilocal settings where co-residing parents relieve the women from household chores.
Keywords: J12; J21; 330; family structure; co-residence; labour supply; patrilocality; Kyrgyzstan